Redesigning A Hybrid Work Scheme To Improve Employee Performance At Pt Bhineka Rahsa Nusantara, Bandung City - Lathifah, Dinar; Nirmalasari, Healthy; Sukoco, Iwan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The significant increase in the hybrid work scheme trend post-Covid-19 pandemic has become a major concern for many companies, including PT Bhineka Rahsa Nusantara. Challenges arise when not all companies have proper management in responding to this work arrangement trend. Therefore, this research aims to assist PT Bhineka Rahsa Nusantara, a startup company in the FMCG industry in Indonesia, in analyzing, evaluating, and redesigning the hybrid work policy. The research method used is qualitative research, which will delve deeper into the components of the hybrid work scheme such as working hours, work flexibility, work environment, and information technology. This research is continued through 4 stages of designing the hybrid work scheme, namely mapping, layering, profiling, and transforming, which ultimately formulated into a policy strategy. Data collection techniques include interviews with internal and external company stakeholders, participatory observation, and documentation studies from primary and secondary sources. The results of this research present analysis, evaluation, and proposals for redesigning the hybrid work scheme based on the perspectives of policy makers, policy managers, and policy recipients that have been adjusted to various applicable regulations. The resulting scheme design consists of policy proposals and documented steps.